2013
DOI: 10.1345/aph.1r725
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Mirtazapine in Fibromyalgia Syndrome Patients: A Randomized Placebo-Controlled Pilot Study

Abstract: Patients with FMS taking mirtazapine exhibited within-group significant improvement in most of the measured outcomes. Between-group analysis was predictably compromised by the small sample size. Mirtazapine was well tolerated. Further study with a larger sample size is likely to be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…With regard to safety, the AE profile of mirtazapine observed in this study was similar to that reported in the double-blind placebo-controlled study of 12-week treatment with 15, 30, or 45 mg/d of mirtazapine in Japanese patients with depression (Study 001), 11 with somnolence being the most frequent AE in both studies. The AEs in our study were also similar to those of the earlier randomized study of mirtazapine in patients with FM, 30 the most common of which were increased appetite and weight gain. In the present study, somnolence of mild or moderate intensity generally occurred in the early phase of treatment (on days 1-14 in 76.8% patients).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…With regard to safety, the AE profile of mirtazapine observed in this study was similar to that reported in the double-blind placebo-controlled study of 12-week treatment with 15, 30, or 45 mg/d of mirtazapine in Japanese patients with depression (Study 001), 11 with somnolence being the most frequent AE in both studies. The AEs in our study were also similar to those of the earlier randomized study of mirtazapine in patients with FM, 30 the most common of which were increased appetite and weight gain. In the present study, somnolence of mild or moderate intensity generally occurred in the early phase of treatment (on days 1-14 in 76.8% patients).…”
Section: Discussionsupporting
confidence: 86%
“…In a placebo-controlled pilot study, Yeephu et al 30 found that there were no significant between-group differences in most efficacy endpoints between the placebo (n = 13) and mirtazapine 15 mg/d (n = 13) or 30 mg/d (n = 14) groups; however, the authors reported that pain VAS, total FIQ, and Jenkins sleep scale scores significantly improved from baseline in each group, particularly the 30 mg/d mirtazapine group. These findings support the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that mirtazapine does not affect gastric compliance, but gastric sensitivity to distention tended to be decreased. Mirtazapine has been used as an analgesic to treat chronic tension‐type headache and fibromyalgia and it was able to ameliorate visceral hypersensitivity and nerve injuries in animal models . The antinociceptive function of mirtazapine has been associated with its combined effect through central serotonergic, noradrenergic, and opioid receptors .…”
Section: Discussionmentioning
confidence: 99%
“…Mirtazapine is a selective antagonist at 5-HT2 and 5-HT3 receptors which also blocks α2 adrenergic auto-receptors in the CNS. In a randomized placebo-controlled pilot study, mirtazapine (30mg per day) exhibited significant within group improvement of pain and FIQ [44]. Thus in contrast, to combined modulation of serotonin and noradrenaline levels, treatments selective for the serotonergic system produced inconsistent outcomes in FM patients.…”
Section: Bioamine Neurotransmittersmentioning
confidence: 98%